Higher DHEA-S (Dehydroepiandrosterone Sulfate) Levels are Associated with Depressive Symptoms during the Menopausal Transition: Results from the PENN Ovarian Aging Study - Morrison, Mary F. (2011)
BACKGROUND: The influence of sex hormones on mood during menopause has been the subject of ongoing investigation. Because dehydroepiandrosterone sulfate (DHEA-S) levels have been associated with several indicators of health outcomes associated with healthy aging, this PENN Ovarian Aging study (POAS) investigation was undertaken to determine the relationship between DHEA-S levels and both depressive symptoms and major depression during the transition through menopause. The original report revealed an unexpected positive correlation between DHEA sulfate (DHEA-S) levels and depressive symptoms in the cohort at baseline. To determine whether the positive association of DHEA-S levels and depression persists in a longitudinal analysis, the cohort was studied over 11 years. METHODS: Longitudinal cohort study with 11 assessments during an 11 year interval in Philadelphia, Pennsylvania. Participants: A randomly identified, population-based sample of 436 African American and Caucasian premenopausal women aged 35 to 47 years at enrollment. Outcome Measures: Center for Epidemiologic Studies Depression Scale score and standardized diagnosis of major depression. RESULTS: In a multivariable model, DHEA-S levels were positively associated with depressive symptoms, when adjusted for age, menopausal stage, race, smoking status and body mass index. There was no relationship between DHEA-S levels and a diagnosis of major depression. CONCLUSIONS: DHEA-S levels were positively associated with depressive symptoms and not with major depression during the menopausal transition.